Algumas aplicações de física do ensino médio a partir do cálculo diferencial e integral - Cruz, Lucas Cavalcanti (2013)
This paper deals with the teaching of topics in Di erential and Integral Calculus in high school. A brief historical analysis of its development, showing some ideas that served for its currently formalization. Some calculus' elements are also de ned to compare them with some intuitive notions or geometric ideas. To nalize it will discuss the importance and usefulness of these issues to other disciplines, particularly physics and how, from some applications, students could understand various concepts in a more simple way and does not require to memorize a huge amount of formulas.